2019
DOI: 10.1162/jocn_a_01392
|View full text |Cite
|
Sign up to set email alerts
|

Medial Orbitofrontal Cortex, Dorsolateral Prefrontal Cortex, and Hippocampus Differentially Represent the Event Saliency

Abstract: Two primary functions attributed to the hippocampus and prefrontal cortex (PFC) network are retaining the temporal and spatial associations of events and detecting deviant events. It is unclear, however, how these two functions converge into one mechanism. Here, we tested whether increased activity with perceiving salient events is a deviant detection signal or contains information about the event associations by reflecting the magnitude of deviance (i.e., event saliency). We also tested how the deviant detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 82 publications
1
39
0
Order By: Relevance
“…This likely explains why we did not observe synchronization using the ISC method, which would require more consistent temporal synchronization from the majority of the participants. Moreover, these results are also consistent with previous work that has found that the vmPFC may be involved in assessing the saliency of a particular event (Jafarpour et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This likely explains why we did not observe synchronization using the ISC method, which would require more consistent temporal synchronization from the majority of the participants. Moreover, these results are also consistent with previous work that has found that the vmPFC may be involved in assessing the saliency of a particular event (Jafarpour et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Stimulation paradigms have implicated the involvement of the vmPFC in the subjective experience of affect, olfaction, and gustation (Fox et al, 2018;Yih et al, 2019). Naturalistic designs, such as passive movie watching, can provide rich contextual information, which makes them well suited for studying social, cognitive, and affective processes (Hasson et al, 2020;Jolly and Chang, 2019;Sonkusare et al, 2019), but have been rarely used in intracranial EEG research (Honey et al, 2012;Jafarpour et al, 2019;Mukamel et al, 2005). The majority of work using naturalistic designs has instead focused on characterizing sensory processes in auditory cortex and found that power in high frequency bands, such as gamma ( ), positively correlate with the envelope of the auditory stimulus (Honey et al, 2012) and also with fluctuations in the BOLD response in auditory cortex of other participants viewing the same stimulus while undergoing fMRI (Mukamel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Discussion SHIN (2020) ___________________________________________________________________________ Pastalkova et al, 2008). Lastly, salient or novel events are shown to engage hippocampal activity (Dolan and Fletcher, 1997;Jafarpour et al, 2019;Kumaran and Maguire, 2006;Ranganath and D'Esposito, 2001). Although we speculate that microstimulation evokes a similar sensation induced by natural stimuli, the initial high intensity of microstimulation might induce a novel sensation that animals had never experienced before.…”
Section: Shin (2020) ___________________________________________________________________________mentioning
confidence: 76%
“…As described for improved auditory perception, the process of accentuation of auditory stimuli that leads to central neural gain may require the co-activation of the basal forebrain to amplify stimulus-induced responses at subcortical and cortical levels ( Figure 3 , BasF blue downward arrow and cross) ( Kilgard et al, 2002 ; Bajo et al, 2014 ; Kraus and White-Schwoch, 2015 ; Irvine, 2018a ). Also, the activation of the inferior frontal gyrus (IFG), as part of the prefrontal cortex (PFC) ( Figure 3 , IFG), is crucial to retaining temporal and spatial associations of auditory events during auditory perception ( Schonwiesner et al, 2007 ; Malmierca et al, 2014 ; Jafarpour et al, 2019 ). In general, the activation of PFC brain regions during perception is crucial to memorizing behaviorally relevant signals and increasing synaptic strength ( Kraus and White-Schwoch, 2015 ; Weinberger, 2015 ; Irvine, 2018b ).…”
Section: Altered Excitation and Inhibition After Acoustic Trauma And Age-related Hearing Loss Are Linked To Increased Central Neural Gainmentioning
confidence: 99%